TRANSPORTING ANTI-CANCER DRUGS THROUGH RED BLOOD CELLS - Isaqova Gavharshod Bahodir qizi; Maxarova Moxinur Baxtiyor qizi; Mirzayeva Dilshoda; Hamroxon Jur‘atova (TADQIQOTLAR, 2025)
Annotation: The use of red blood cells (RBCs) as carriers for anti-cancer drugs has emerged as a promising strategy to improve therapeutic efficacy while reducing systemic toxicity. Encapsulation or surface loading of chemotherapeutic agents within RBCs  allows  for  controlled  drug  release,  prolonged  circulation  time,  and  targeted delivery  to  tumor  tissues.  This  approach  exploits  the  natural  biocompatibility  and immune  evasion  properties  of  RBCs,  potentially  overcoming  limitations  of conventional  drug  delivery  systems.  Recent  studies  have  demonstrated  enhanced pharmacokinetics,  reduced  adverse  effects,  and  improved  tumor  suppression  using RBC-based carriers in both preclinical and early clinical settings. However, challenges remain  in  large-scale  manufacturing,  drug-loading  efficiency,  and  ensuring  safety across diverse patient populations. Continued research into engineering techniques, optimization of drug-RBC interactions, and integration with other targeted therapies could establish RBC-mediated delivery as a transformative tool in oncology.